Pembelajaran IPAS Berbasis Potensi Lokal Pisang Untuk Meningkatkan Ecoliteracy Siswa Kelas 4 SD - Eko Setiyawan Dwipranoto; Sudarti; Rusdhianti Wuryaningrum (Elementary Teacher Education Program, Majalengka University, 2023)
Education is expected to not only assess cognitive aspects but can develop students' character who cares about the environment in the era of globalization and increasingly advanced technology. Technological advances have an impact on reducing concern for the environment, this is what encourages learning to use the potential of the school environment to help encourage environmental awareness by increasing students' ecoliteracy insight at SD Negeri Kaliwungu 03, especially grade 4 through science subjects. This research was conducted at SD Negeri Kaliwungu 03 using the pre-experimental design method. The resulting data was analyzed using Paired Sample t-Test. The results for 11 indicators in 3 aspects from 10 respondents showed that the average value of the observation results increased from 19.90 to 28.50 with a significance value in the Paired Sample t-Test test which obtained a result of 0.000 and this value was <0.05. Based on the research that has been carried out, it can be concluded that there has been an increase in students' understanding of ecoliteracy after visiting banana processing places around the school. In this way, learning science and technology using the local potential of bananas can be said to provide an increase in the ecoliteracy of students at SD Negeri Kaliwungu 03.